RESISTANCE FOR TRUTH IN NICOLA YOON’S NOVEL EVERYTHING, EVERYTHING - Siska Dewi Rahayu; Sri Wulan (JOURNAL OF LANGUAGE, 2019)
This study is concerned with the resistance of the protagonist. The protagonist, Madeline Whittier has a great bravery to resist rules and fear to find the truth although she is still teenager. The protagonist’s form of resistance and truth are formulated in the statement of the problem. Various theories are adapted to support the analysis, and one of which was proposed by Eric and Jay in theirs book Resistance and Persuasion. The method used in this study is qualitative. The method gives a significant portrayal of the protagonist’s resistance. The findings of this study are two forms of resistance done by the protagonist, i.e. resisting her mother’s rules and resisting her own fear. Such resistance results in the truth that the protagonist discovers. First is about her true disease, and second her mother’s lies to her for seventeen years. In conclusion, the protagonist conducts resistance to find truth of her own life.